Mycoinsecticides for aphid management: a biorational approach - Yeo, Helen (2000)
This study considered a novel approach to selecting isolates of Hyphomycete fungi as mycoinsecticides for biological control of aphids in arable crops in the UK. The approach was designed to select isolates which were compatible with both the biotic and abiotic environment.